What is the clinical benefit of left main coronary artery treatment by percutaneous coronary intervention?. (2nd May 2022) - Costa, H; Fernandes, R; Mota, T; Santo, ME; Palmeiro, H; Bispo, J; Carvalho, D; Guedes, J; Mimoso, J; Vinhas, H; Jesus, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The treatment of choice of left main coronary artery (LMCA) disease has been subject to intense debate and investigation in the last decade. More recent studies showed benefit of percutaneous coronary intervention (PCI) in patients with less complex coronary anatomy. Although it is not the standard treatment, the use of this technique has been increasing. Objectives: Characterize the patient population undergoing LMCA PCI and analyze its clinical benefit. Also, try to identify patient profiles according to the composite outcome (angor, heart failure symptoms (HF), myocardial infarction (MI) or death) in short and medium term (30 days (D) and 180D). Methods: Observational and retrospective study of patients submitted to LMCA PCI, between 1 January 2019 and 31 December 2020. A descriptive analysis was carried out. Chi-Square test was used for categorical variables and the T-Student test for numerical variables, with a significance level of 95%. CHIAD algorithm was applied to identify patient profiles – composite outcome was the dependent variable (fixed 15 parent nodes and 5 children nodes). For statistical analysis, SPSS 24.0 was used. Results: N120 patients, mean age of 70, 4 years (standard deviation of 10.8), 76% were male. 81.7% had multivessel disease, with LMCA-anterior descendig artery injury being the most frequent (31.7%). The average LVEF was 49%. The complication rate was 15.8%, most vessel dissections. The most serious complications (cardio-respiratory arrest and cardiogenic shock) occurred in 0.8% of cases. The composite outcome occurred in 25, 2% (30D) and 13, 3% (180D), regardless of past medical history and number/type of vessels affected. The presence of angor was 9.9% (30D) and 1.3% (180D); HF symptoms in 13.5% (30D) and 4.8% (180D); MI in 2.7% (30D) and 1.2% (180D) and mortality in 2.7% (30D) and 2.4% (180D). In a logic of dependence and profiles, patients with LVEF [45-55%] (95.6%-p=0.003) who treated the lesions in first intention (AdHoc) (100%-p=0.009) presented fewer occurrences at 30D. Patients with occurrences at 30D (65.2%-p=0.001) or without PV of LVEF (66.7%-p = 0.016) and dyslipidemia (53.8%-p = 0.027) were those with most occurrences at 180D. Conclusion: This analysis highlights the experience of the angiography laboratory. The majority of patients experienced evident clinical improvement and recovered in shortand medium term. The rate of serious events was low. The analysis suggests that the greatest benefit were found in the profile of patients with LVEF [45-55%] with an AdHoc approach.